Compassionate care and moral distress in nursing: the mediating role of organizational citizenship behavior - Somaye Mohammadi; Mahnaz Rakhshan; Mostafa Roshanzadeh; Parvin Ghaemmaghami; Hamid Reza Hamidian (Journal of Medical Ethics and History of Medicine)
Decline in compassionate care is potentially linked to moral distress and fostering different aspects of organizational citizenship behavior can reduce the outcome of moral distress. This study aimed to determine the mediating role of organizational citizenship behavior in the relationship between compassionate care and moral distress among nurses. For this purpose, a correlational study design using structural equation modeling was employed. Between December 2023 and March 2024, 300 nurses were selected through convenience sampling from hospitals in Fars Province, southern Iran. Data were collected using the Organizational Citizenship Behavior Questionnaire, the Compassionate Care Questionnaire for Nurses, and the Moral Distress Questionnaire. Data analysis was conducted using SPSS version 22 and Smart-PLS software.Our findings showed that compassionate care, combined with the mediating role of organizational citizenship behavior, significantly impacted moral distress (t = 2.442, P < 0.015, β = -0.071).  Pearson’s correlation coefficients showed that compassionate care had a positive and significant relationship with organizational citizenship behavior (r = 0.444, P < 0.001) and a negative and significant relationship with moral distress (r = -0.353, P < 0.001).It is therefore recommended that managers in clinical systems focus on training nurses who exhibit appropriate organizational citizenship behavior in health-care settings.